2016
DOI: 10.1177/0040517515581588
|View full text |Cite
|
Sign up to set email alerts
|

Balloon theory of yarn during unwinding from packages

Abstract: Yarn unwinding from a package is a key problem in many textile processes, such as weft insertion and warping. Stability of the unwinding has a direct influence on the efficiency of the entire textile process and the quality of the final product. The quality of the yarn is numerically expressed mainly in terms of mechanical quantities. In the unwinding process, viscoelastic properties are the most important. They depend on how the yarn is stressed. The quality of the yarn that is being unwound should not be red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…In the device from [6], a source of illumination is the laser beam that scans a bobbin surface, which allowed a considerable increase in resolution.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…In the device from [6], a source of illumination is the laser beam that scans a bobbin surface, which allowed a considerable increase in resolution.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The device described in [6] is the development of systems based on scanning the image of a bobbin by the laser beam, such as Beltro-Lis [7], manufactured by Barmag AG (Germany). The system records the presence of torn elementary threads, stains and dirt, as well as controls the contours of packings.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Because the equations are expressed in a (nonuniformly) rotating observation frame, they can be used to describe yarn unwinding from stationary packages. 16 Pracek et al 17 deduced the differential equation of motion for yarn unwinding on a cylindrical surface, which can be applied to the analysis of yarn unwinding in the textile process. However, limited research has been found around the polyester filament winding process.…”
mentioning
confidence: 99%
“…The quality of yarn is affected by many factors, such as high-frequency vibration, 5 friction forces, 6 and air resistance. 7 The dynamics simulation is an important means to understand yarn dynamic behavior. The viscoelasticity of yarn, gravity, and air resistance are three important roles that affect yarn's dynamic behavior, and they should be given full consideration.…”
mentioning
confidence: 99%
“…In recent years, the dynamic behavior of yarn has been studied more and more deeply. Pracˇek and Pusˇnik 6 and Pracˇek et al 7 set up a yarn motion equation to analyze the stress of the yarn during the unwinding process of stress, taking into account the Coriolis force, the centripetal force, and the Euler force, but the influence of yarn cross-section diameter, gravity, and tangential air resistance were not considered. Hossain et al 10 analyzed the kinematic characteristics of the yarn in the spinning process.…”
mentioning
confidence: 99%